2018
DOI: 10.1111/imj.13973
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic fatty liver disease patients attending two metropolitan hospitals in Melbourne, Australia: high risk status and low prevalence

Abstract: NAFLD constituted a minority of liver clinic patients, most of who were obese, insulin resistant and hypertensive, and many had an elevated liver stiffness measurement. NAFLD poses added adverse health outcomes to high-risk patients, and therefore, early detection is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
2
9
0
1
Order By: Relevance
“…Taken together, the present results and data of Chow et al . confirm that it is potentially erroneous to assume that a single LSM that exceeds 12 kPa (but is less than 30 kPa) indicates the patient has “at least moderate fibrosis” in NAFLD: Alternatively, such cases may have severe steatosis and/or mild NASH with potential for an excellent response to lifestyle modification, even when only modest adjustments in weight and physical activity are achieved …”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Taken together, the present results and data of Chow et al . confirm that it is potentially erroneous to assume that a single LSM that exceeds 12 kPa (but is less than 30 kPa) indicates the patient has “at least moderate fibrosis” in NAFLD: Alternatively, such cases may have severe steatosis and/or mild NASH with potential for an excellent response to lifestyle modification, even when only modest adjustments in weight and physical activity are achieved …”
Section: Resultssupporting
confidence: 70%
“…Table details the numerous studies that have proposed cutoff values for liver stiffness by FibroScan in NAFLD. While earlier studies often suggested that > 9.5 or 12.5 kPa indicates “at least moderate risk of significant liver fibrosis” or “high risk of cirrhosis in NAFLD,” more recent data indicate that the cutoff for advanced liver fibrosis in NAFLD is not the same as for viral hepatitis . Further, initial measurements may not reflect a stable change .…”
Section: Liver Stiffness Measurement In Non‐alcoholic Fatty Liver Dismentioning
confidence: 96%
“…We read with interest the article by George et al describing non‐alcoholic fatty liver disease (NAFLD) in liver clinics of two metropolitan Melbourne teaching hospitals . While their finding that obesity and glucose intolerance are the usual risk factors for significant liver disease with NAFLD is well supported by the literature, we were surprised that NAFLD formed only 7% of referrals to those clinics.…”
mentioning
confidence: 90%
“…Australia is well placed to conduct collaborative studies such as those needed to test promising biomarker and physical investigations that characterise those patients in need of major interventions. In the meantime, we strongly agree that greater public and professional awareness of fatty liver as a common accompaniment of overweight and metabolic obesity is needed . Given the strong links between NAFLD and risk of type 2 diabetes, cardiovascular disease and common cancers, even those cases in which the liver disease is minor can benefit enormously from lifestyle intervention, irrespective of whether referral to a liver clinic is activated or not.…”
mentioning
confidence: 96%
“…NAFLD is a systemic condition, featuring metabolic, cardiovascular, and (hepatic/extrahepatic) cancer risks [1,2]. NAFLD is the most frequent cause of chronic liver injury in adults in developed countries [3,4]. About one-quarter of fatty liver cases develop NASH and over one-quarter of NASH patients develop severe fibrosis [1,5,6,7].…”
Section: Introductionmentioning
confidence: 99%